2003
DOI: 10.1007/s00103-003-0693-3
|View full text |Cite
|
Sign up to set email alerts
|

?-Laktamasen mit breitem Wirkungsspektrum

Abstract: Plasmidkodierte AmpC-β β-LaktamasenDiese Enzyme hydrolysieren 7-α-methoxy-Cephalosporine (Cephamycine, wie z. B. Cefoxitin und Cefotenan). Sie werden nicht oder nur gering durch sitespezifische β-Laktamase-Inhibitoren geAbb. 1 Übersichtsschema zur Unterteilung von β β-Laktamasen. (TEM β β-Laktamase vom TEM-Typ, SHV β β-Laktamase vom SHV-Typ, OXA β β-Laktamase vom OXA-Typ, Gram Ø gramnegativ, Metallo Metallo-β β-Laktamase, Serin Serin-β β-Laktamase)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…As a result, they retain activity against a wide variety of resistant pathogens and this is of importance, as the incidence of resistant strains expressing ESBLs is increasing. [7][8][9][10] Few data are available about the in-hospital experience of clinicians treating sepsis, on their perceived use of carbapenems in sepsis, prescription pattern and clinical outcome with the use of carbapenems in tertiary care hospital for sepsis management. This study was undertaken with the objective of knowing the importance of carbapenems in the management of sepsis focusing on perceived use and the clinical outcome in real time setting in intensive care in and around Mangalore, India.…”
Section: Figure 1: Major Pathogens Isolated From Indian Sepsis Patientsmentioning
confidence: 99%
“…As a result, they retain activity against a wide variety of resistant pathogens and this is of importance, as the incidence of resistant strains expressing ESBLs is increasing. [7][8][9][10] Few data are available about the in-hospital experience of clinicians treating sepsis, on their perceived use of carbapenems in sepsis, prescription pattern and clinical outcome with the use of carbapenems in tertiary care hospital for sepsis management. This study was undertaken with the objective of knowing the importance of carbapenems in the management of sepsis focusing on perceived use and the clinical outcome in real time setting in intensive care in and around Mangalore, India.…”
Section: Figure 1: Major Pathogens Isolated From Indian Sepsis Patientsmentioning
confidence: 99%
“…As a consequence, they retain activity against a wide variety of multiply resistant pathogens, especially cephalosporin‐resistant Gram‐negative bacteria. This is of importance, as the incidence of strains expressing ESBLs (and often more than one ESBL per organism) is increasing [5–8]. For example, the Paul‐Ehrlich‐Society’s multicentre survey on resistance, which has been conducted on a regular basis since 1975, reported, for the years 2001 and 2004, ESBL phenotypes in 1.8% and 5.1% of Escherichia coli, in 12.7% and 7.3% of Klebsiella pneumoniae, and in 5.3% and 12.4% of Klebsiella oxytoca isolates, respectively [9].…”
Section: Microbiologymentioning
confidence: 99%
“…Note however that the PEG-study in 2001 already revealed a cefotaxim-resistance rate of 11% for Klebsiella pneumoniae. We know from countries in which Enterobacteriaceae with ESBL occurred much earlier that K. pneumonia was always effected first and acted as a reservoir for the b-lactamase genes and resistance plasmids, followed by E. coli later on (Witte and Mielke, 2003).…”
mentioning
confidence: 99%